(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article presents the opinions of domestic and foreign scientists on modern methods for developing network attack detection systems. "Network attack detection systems" refers to systems designed to identify, monitor, and respond to unauthorized or malicious activities within a computer network. These systems aim to protect the network from potential security breaches or attacks. Common examples include Intrusion Detection Systems (IDS) and Intrusion Prevention Systems (IPS). The article presents a comparative analysis of network access detection systems.